1997
DOI: 10.1103/physrevb.56.7763
|View full text |Cite
|
Sign up to set email alerts
|

Lattice dynamics of crystals havingR2MX6structure

Abstract: The theory of lattice dynamics in the harmonic approximation using a rigid-ion model due to Born and Huang ͓Dynamical Theory of Crystal Lattices ͑Oxford University Press, New York, 1954͔͒, is applied to ionic crystals of the R 2 M X 6 type with antifluorite structure namely, K 2 SnCl 6 , K 2 PtBr 6 , Cs 2 SnBr 6 , and Rb 2 SnBr 6 in the cubic phase. The model expresses the potential energy as the sum of long-range Coulomb interactions and repulsive short-range interactions between ions in the primitive cell. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…[ 39 ] Due to the alternate vacant octahedra in A 2 BX 6 , the whole octahedra can vibrate as a rigid body resulting in a third IR active mode of vibration. Three IR active mode of vibration for the R 2 MX 6 crystal structure was also reported by Torres et al [ 40 ] The highest, intermediate, and lowest wavenumber vibrational peaks were assigned to X‐Sn asymmetric stretching, X‐Sn‐X asymmetric bending and vibration of [SnX 6 ] 2− octahedra as a rigid body against Cs + cation respectively. [ 41 ] The Cs 2 PtCl 6 showed three IR active peaks at 328, 184, and 67 cm −1 (Figure 1b) and the peaks are assigned to Pt–Cl asymmetric stretching, Cl–Pt–Cl asymmetric bending and vibration of [PtCl 6 ] 2− octahedra as a rigid body, respectively.…”
Section: Resultssupporting
confidence: 61%
“…[ 39 ] Due to the alternate vacant octahedra in A 2 BX 6 , the whole octahedra can vibrate as a rigid body resulting in a third IR active mode of vibration. Three IR active mode of vibration for the R 2 MX 6 crystal structure was also reported by Torres et al [ 40 ] The highest, intermediate, and lowest wavenumber vibrational peaks were assigned to X‐Sn asymmetric stretching, X‐Sn‐X asymmetric bending and vibration of [SnX 6 ] 2− octahedra as a rigid body against Cs + cation respectively. [ 41 ] The Cs 2 PtCl 6 showed three IR active peaks at 328, 184, and 67 cm −1 (Figure 1b) and the peaks are assigned to Pt–Cl asymmetric stretching, Cl–Pt–Cl asymmetric bending and vibration of [PtCl 6 ] 2− octahedra as a rigid body, respectively.…”
Section: Resultssupporting
confidence: 61%
“…Structural PropertiesRb2SnBr6 crystallized in face-centered cubic crystal with space group Fm-3m (#225) is shown in Figure1. The optimized lattice parameter is 10.75 Å which is near to the investigational (Å[25].…”
mentioning
confidence: 75%
“…Room-temperature Raman analysis of the fabricated films was performed using 633 nm excitation wavelength to complement the XRD results and probe the vibration property of the I 2 -rich Cs 2 SnI 6 film. Theoretical studies [42,43] have suggested that the ten normal modes are present in the vibrational spectrum, including one IR active, one acoustic, two silent, and four Raman active. Among the active Raman modes in Cs 2 SnI 6 perovskite, three are associated with [SnI 6 ] 2À octahedral and one is related to the vibration of Cs atoms in the rigid [SnI 6 ] 2À lattice.…”
Section: Resultsmentioning
confidence: 99%